Mawlana zada rifaat bag 1869-1930 his life and political role - Ismail, Warhel (Humanities Journal of University of Zakho, 2023)
It’s clear that study and maneuvering of historical biography is a significant aspects of history of nowadays, studying of biography and story that related to those duties which people worked in had moved through many great events of history, they have been ignored through historical study and been neglected in history. However, it needs to say that history is deeply a science of braver’ and persons, as they played a great role in history especially during crisis and limited events, studying history has not had a point without taking persons and leaders into considerations. This idea could be taken into account on this study, which is entitled “Mawlana Zada Rifaat Zada Bag 1869-1930: his life and political role”, biography of this person related to many clandestine event, which were related to the Ottoman state constitution during the first decade of twenty centuries, also political and cultural life of Kurds, Mawlana Zada was the first Kurdish nationalist generation, who struggled in favor of Kurdish land (Kurdistan) in the political map of the new Middle East, biography of this Kurdish person related to the transformation of political event of the Ottoman state, particularly after the Ottoman coup date of July 1908, furthermore the internal challenges between ethnics of the Ottomans state, these event moved nations particularly Kurds , Turks and Armens to divide Ottoman state in Kurdistan, Anatolia which Mawlana Zada Rifaat lived. Mawlana Zada Rifaat lived during the greatest transformation that were happened in the Ottoman state and Kurdistan, this period conducted from the July 1980 coup continued till the First World war and ended when the new Turkish Republic established in 1923 by Mustafa Kamal Pasha, this study attempts to answer some questions such as: What factors influenced Mawlana Zada Rifaat’s ideas? What was his attitude to the second Sulltan Abdulhamid 1876-1909? Did he support the 1908 coup d’état of youngest Turks or he stand against it? How his Kurdish national idea developed? Did he support the establishment of Kurdistan state and held the Ottoman idea? Why his attitude was effectively strong to Kamal Mastafa Pasha and Turkish new state? How was his life looked like at the end? this study has many questions and had answered these questions according to documents and historical references.